KEADILAN RESTORATIF DALAM PENYELESAIAN PERKARA ANAK YANG BERHADAPAN DENGAN HUKUM DALAM SISTEM PERADILAN PIDANA ANAK - Andri Winjaya Laksana (Jurnal Pembaharuan Hukum, 2017)
Restorative justice in the settlement of cases of off-the-shelf criminal offenses emphasizing the rearation of the consequences caused by criminal acts by empowering the recovery process and the interests of all involved both perpetrators and victims, as well as the public. The caseresolution model outside the court proceedings is a method that is expected to be undertaken to protect the psychology of a child facing the law in the criminal justice system